Partial Least Square In Analyzing The Influence Of Service Quality, Facilities And Price On Customer - Mohammad Saefus Sholeh; Ribangun Bamban Jakaria (Procedia of Engineering and Life Science, 2021)
UD Barokah Tiga is a business that sells building materials and electric tools. The aim of this research is to measure how the influence of service quality, facilities and price affects customer satisfaction. The research that will be conducted here uses the Partial Least Square (PLS) method using the Warppls 7.0 software. The results of this study for service quality variables have a significant influence on customer satisfaction variables. Because it has a P-value of 0.001 from <0.05. For the value obtained X1 5,346 where> from 1.96 where for X1 has a significant value. The facility variable does not have a significant effect on the customer satisfaction variable. Because it has a P-value of 0.15 from <0.05. For the value obtained X2 1.054 where <from 1.96 where for X2 has an insignificant value. The price variable has a significant influence on the consumer satisfaction variable. Because it has a P-value of 0.001 from <0.05. For the value obtained X3 4,645 where> from 1.96 where for X3 has a significant value